The Influence of Liquid Medium Choice in Determination of Minimum Inhibitory Concentration of Essential Oils against Pathogenic Bacteria - Radka Hulankova (MDPI AG, 2022)
So far there is no internationally accepted, standardized method for MIC determination of natural substances such as essential oils (EOs). The aim of this study was to elucidate how much the MIC values obtained from various studies using different culture media are comparable. The median MICs for cinnamon essential oil (EO) obtained by broth dilution were 517, 465 and 517 µg/mL for Mueller-Hinton Broth (MHB), Tryptone Soya Broth (TSB) and Brain Heart Infusion (BHI), respectively. The MIC values for oregano EO were significantly (p < 0.001) lower in MHB than in highly nutritious media; the median MICs were 616 µg/mL for MHB and 474 µg/mL for TSB and BHI. This statistically significant difference was noted for all the pathogens studied (Salmonella Enteritidis, Escherichia coli O157, Listeria monocytogenes, Staphylococcus aureus). In the presence of oregano EO lag phase was also much less prolonged in MHB (by 6-17%) than in the other media (by 92-189%). Some components of EOs may bind to starch in MHB; since the phenomenon seems to be selective and EO dependent, the use of MHB for comparison of antimicrobial properties of various EOs thus cannot be recommended.